mHealth app for monitoring relapse in the use of licit and illicit substances linked to a health service (Research, Society and Development, 2022)
Objective: The objective of this article is to present the process of creating a prototype of the application (App) mHealth, called APTAD Natal. The App is aimed at patients who are addicted to cigarettes, alcohol and/or illicit drugs treated at the outpatient Clinic for the Prevention and Treatment of Tobacco, Alcoholism and Other Drug Addictions (APTAD), located in the city of Natal, Brazil. The prototype is intended to help monitor relapses through self-monitoring and family supervision, so that the patient remains abstemious and, thus, reduces risk factors for Chronic Noncommunicable Diseases. Method: The research practice of Participatory Design was used, aiming at raising the awareness of professionals from the multidisciplinary team of the health service regarding the use of Information and Communication Technology (ICT) tools. Results: The prototype of the mHealth APTAD Natal application was successfully delivered to professionals from the multiprofessional team to patients treated at the outpatient clinic and to their families. The instrument stands out for innovating in providing therapeutic support to the three most prevalent addictions: smoking, alcoholism and use of illicit substances, in addition to working integrated with the Electronic Health Record already in use at the outpatient clinic. Conclusion: Through the sharing of difficulties and experiences of health professionals and the use of ICT and mHealth tools (Mobile Health), it is possible to innovate and increase the reach of therapeutic interventions remotely through mHealth applications, which assist in the treatment of patients daily, 24 hours a day.